Energy and Carbon Loss Management in an Electric Bus Factory for Energy Sustainability - Savran, Efe; Yavaş, Özcan; Erolnalbur, Berrak; Karpat, Fatih (Transdisciplinary journal of engineering & science, 2022)
Increasing energy need brings people one step closer to energy saving and alternative sources. The search for reliable and sustainable resources also contributes greatly to technological progress. Thanks to advanced technology, energy use becomes more efficient. However, the concept of sustainability emerges in the field of energy as in other sectors. It is expected that electric vehicles, which have started to increase in interest in recent years, will make a positive contribution to issues such as environmental protection and sustainable energy.  In addition, production centers for electric vehicles should also be sustainable and sensitive to carbon emissions. In this study, energy and carbon loss assessment was carried out in an electric bus manufacturing factory. With the help of linear regression analysis, the data of the last 3 years were evaluated. Moreover, as a result of internal audits, energy loss points were determined. As a result of this study, sustainability, carbon loss, and energy management issues in an electric vehicle production factory were evaluated and guiding qualities for today's and future technology companies were revealed.